Strength as a predictor of aerobic power in competitive cyclists: national team insights - Javaloyes, A.; Sánchez-Muñoz, C.; Salas-Montoro, J. A.; Moya-Ramón, M.; Mateo-March, M. (International Journal of Sports Medicine, 2025)
Maximal aerobic power (MAP) and time-to-exhaustion at MAP are critical for cycling performance, yet the role of maximal lower-body strength in enhancing these metrics across sex, category, and discipline in cyclists remains underexplored. This study investigated the relationships between 1RM, MAP, and time-to-exhaustion at MAP in 69 high-level and professional cyclists from the same national team, stratified by sex, category, and discipline. Cyclists underwent a two-day protocol to assess MAP via a graded exercise test, time-to-exhaustion at MAP, and 1RM via a velocity-based parallel back squat test. Spearman correlations, mixed models, generalized additive models, structural equation modeling, and cluster analysis examined strength-performance relationships, adjusted for covariates. 1RM strongly predicted MAP (r=0.73, ß=0.86, p<0.001; 2.47 W increase per kg), and relative 1RM predicted MAP relative to body mass non-linearly (r=0.58, ß=0.84, p<0.001). Time-to-exhaustion showed no significant strength association (p>0.05). Women exhibited lower MAP (-71.67 W, p<0.001), mountain bike cyclists showed longer time-to-exhaustion (+0.61 SD, p=0.049), and elite cyclists had higher MAP (+21.51 W, p=0.030), reflecting physiological and discipline-specific differences. Clusters highlighted strength-power distinctions. These findings demonstrate that maximal strength is associated with MAP but not time-to-exhaustion, with associations varying according to sex, discipline, and category.